2018
DOI: 10.1542/peds.2018-1076
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Use by Breastfeeding Mothers and Cannabinoid Concentrations in Breast Milk

Abstract: ∆9-THC was measurable in a majority of breast milk samples up to ∼6 days after maternal marijuana use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
74
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(78 citation statements)
references
References 24 publications
1
74
0
1
Order By: Relevance
“…During the early postnatal period, breastfeeding by cannabis-using mothers actively transfers the principle psychoactive component of cannabis, ∆9-tetrahydrocannabinol (THC) and other cannabinoids to the developing infant, as the lipophilic nature of these cannabinoids results in concentrations in breast milk which are equal to or exceeding that found in the plasma of the user 7,8 . Importantly, this transfer may persist well beyond the intoxication period of the user due to the long half-life of THC in breast milk 9 , thus occluding the possibility of simply breastfeeding outside of the acute cannabis consumption period as is often done with alcohol consumption 10 . Therefore, understanding and disseminating data regarding the consequences of THC consumption during the breastfeeding period is paramount to public health in the evolving age of cannabis use.…”
Section: Introductionmentioning
confidence: 99%
“…During the early postnatal period, breastfeeding by cannabis-using mothers actively transfers the principle psychoactive component of cannabis, ∆9-tetrahydrocannabinol (THC) and other cannabinoids to the developing infant, as the lipophilic nature of these cannabinoids results in concentrations in breast milk which are equal to or exceeding that found in the plasma of the user 7,8 . Importantly, this transfer may persist well beyond the intoxication period of the user due to the long half-life of THC in breast milk 9 , thus occluding the possibility of simply breastfeeding outside of the acute cannabis consumption period as is often done with alcohol consumption 10 . Therefore, understanding and disseminating data regarding the consequences of THC consumption during the breastfeeding period is paramount to public health in the evolving age of cannabis use.…”
Section: Introductionmentioning
confidence: 99%
“…Both the American Academy of Pediatrics and American College of Obstetricians and Gynecologists currently recommend counseling the mother to abstain from all cannabis products if desiring to breastfeed. 7,8 With their study, Bertrand et al 3 have provided additional and valuable support for those current recommendations. But the picture is incomplete without our understanding of what is happening at the level of those infants exposed to cannabinoid-containing breast milk.…”
mentioning
confidence: 84%
“…Until now, the scientific evidence that would be used to help a provider make an informed decision has been essentially nonexistent. Thus, the study reported by Bertrand et al 3 in this current edition of Pediatrics, entitled "Marijuana Use by Breastfeeding Mothers and Cannabinoid Concentrations in Breast Milk, " is timely and important, because it provides, for the first time, data from a large sample of human milk donors (N = 50) who were currently breastfeeding and using cannabis products, both smoked and edible.…”
mentioning
confidence: 99%
See 2 more Smart Citations